A perfeição da justiça em Platão uma análise comparativa entre a alegoria da linha dividida e os personagens d A República - Lima, Jorge dos Santos (2007)
The allegory of the divided line presents one structure that divides itself into four levels of reality. Two of them move in the world of appearances or opinion, and the others into the world of being or intelligibility: eikasia and pistis, and dianoia and noesis. The difficulty is the following: if there are four levels of reality each with their respective objects that are apprehended according to a type of knowledge involved, is there an interpretation of the justice according to each level? Accordingly, our intention, after presenting the types of knowledge in the allegory of the divided line, is to demonstrate how the justice is comprehended at each level of reality. We understand that Plato uses the characters to represent levels involving different types of knowledge. The characters are Cephalus, Polemarchus, Thrasymachus, Glaucon, Adimantus and Socrates, and the comprehension about what is the justice at each level follows what these characters understand justice to be